Memorials, North East corner - Ghosh, Ayan (2023)
The memorials carry an epitaph eulogizing the qualities of the deceased person and mention what position or rank they held in society (or in the military), their age, place, circumstances, and date of death. Some memorials have funerary art designed in the Neoclassical style, showing portraiture, funerary urns, military symbols, or allegorical figures in mourning.